2012
DOI: 10.1152/japplphysiol.00565.2012
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-induced opening of intrapulmonary arteriovenous anastomoses in healthy humans at rest

Abstract: The mechanism or mechanisms that cause intrapulmonary arteriovenous anastomoses (IPAVA) to either open during exercise in subjects breathing room air and at rest when breathing hypoxic gas mixtures, or to close during exercise while breathing 100% oxygen, remain unknown. During conditions when IPAVA are open, plasma epinephrine (EPI) and dopamine (DA) concentrations both increase, potentially representing a common mechanism. The purpose of this study was to determine whether EPI or DA infusions open IPAVA in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 60 publications
(78 reference statements)
3
94
1
Order By: Relevance
“…The existence of IAAV that bridge pulmonary arteries and veins has been identified in the late-gestation fetus (13)(14)(15), but IAAV are believed to disappear during the late neonatal period (15), and their potential physiologic roles are controversial. Such vessels have been suggested as contributing to intrapulmonary shunt in adults during catecholamine infusion, with exercise, and in an older patient with BPD (11,12,(25)(26)(27)(28)(29). Our findings support the hypothesis that IAAV are prominent and persist in the preterm infants with severe BPD and our speculation that such vessels contribute to hypoxemia from intrapulmonary anastomoses with sustained respiratory insufficiency in severe BPD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The existence of IAAV that bridge pulmonary arteries and veins has been identified in the late-gestation fetus (13)(14)(15), but IAAV are believed to disappear during the late neonatal period (15), and their potential physiologic roles are controversial. Such vessels have been suggested as contributing to intrapulmonary shunt in adults during catecholamine infusion, with exercise, and in an older patient with BPD (11,12,(25)(26)(27)(28)(29). Our findings support the hypothesis that IAAV are prominent and persist in the preterm infants with severe BPD and our speculation that such vessels contribute to hypoxemia from intrapulmonary anastomoses with sustained respiratory insufficiency in severe BPD.…”
Section: Discussionsupporting
confidence: 87%
“…Previous physiologic data suggest that right-to-left intrapulmonary shunt pathways exist in adults, as demonstrated by echocardiographic studies during exercise, with exposure to hypoxia and during infusions of catecholamines (12,(26)(27)(28)(29). Furthermore, IAAV are present in pathologic conditions in adult lungs after cavopulmonary shunt operations (30) and with hepatopulmonary syndrome (31).…”
Section: Discussionmentioning
confidence: 94%
“…The subjects with CHF in this study were taking several medications, including β-blockers. We have previously shown that hypoxia-induced shunting through IPAVA is not impacted by β-blockade when changes inQ T are relatively minimal (Laurie et al 2012). However, a doubling ofQ T caused by catecholamine infusion can increaseQ IPAVA when subjects without PFO are breathing room air and 40% O 2 (Elliott et al 2014).…”
Section: A T Lovering and Othersmentioning
confidence: 97%
“…Saline contrast echocardiography was performed at rest, as detailed previously, to detectQ IPAVA (Laurie et al 2010(Laurie et al , 2012Elliott et al 2011;. Briefly, a 20-or 22-gauge I.V.…”
Section: Echocardiographic Screening and Saline Contrast Echocardiogrmentioning
confidence: 99%
“…4 The fact that only brief periods of hyperoxia are needed suggests that O 2 acts locally on the vasculature. Recently, Laurie et al 12 echocardiographically observed IPAVs in a group of healthy adults infused with epinephrine, evidenced by the observation of agitated bubble contrast in the left ventricle .5 cardiac cycles after right heart opacification. Right-to-left bubble passage was eliminated by 100% O 2 breathing.…”
mentioning
confidence: 98%